1999
DOI: 10.1152/ajpheart.1999.276.1.h300
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ca2+release and entry during contraction elicited by norepinephrine in rat resistance arteries

Abstract: Lagaud, G. J. L., V. Randriamboavonjy, G. Roul, J. C. Stoclet, and R. Andriantsitohaina. Mechanism of Ca 2ϩ release and entry during contraction elicited by norepinephrine in rat resistance arteries. Am. J. Physiol. 276 (Heart Circ. Physiol. 45): H300-H308, 1999.-The intracellular Ca 2ϩ stores and the mechanisms of Ca 2ϩ entry produced by norepinephrine (NE) were investigated in small mesenteric resistance arteries of the rat. In Ca 2ϩ -free medium, NE (10 µM) elicited a transient increase in both intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 34 publications
6
53
0
2
Order By: Relevance
“…Tyrosine phosphorylation has been shown to be associated with Ca 2ϩ entry through VDCC (Wijetunge et al, 1992(Wijetunge et al, , 1998Lagaud et al, 1999). A recent study has specifically shown the involvement …”
Section: Downloaded Frommentioning
confidence: 98%
See 1 more Smart Citation
“…Tyrosine phosphorylation has been shown to be associated with Ca 2ϩ entry through VDCC (Wijetunge et al, 1992(Wijetunge et al, , 1998Lagaud et al, 1999). A recent study has specifically shown the involvement …”
Section: Downloaded Frommentioning
confidence: 98%
“…Consistently, tyrosine kinase inhibitors have been shown to attenuate vasoconstriction caused by a number of agents, including noradrenaline and angiotensin II in intact arteries (Di Salvo et al, 1993Laniyonu et al, 1994;Carmines et al, 2001). Recent studies have shown that the voltage-dependent Ca 2ϩ channels (VDCCs), activated by many vasoactive agents, are inhibited by tyrosine kinase inhibitors via tyrosine kinases (Wijetunge et al, 1992;Wijetunge et al, 1998;Lagaud et al, 1999). In addition to the effects on Ca 2ϩ channels, tyrosine kinases may regulate other mechanisms controlling the contractile state of smooth muscle cells.…”
mentioning
confidence: 97%
“…High-resolution echocardiography analysis was performed using a Vevo2100-high resolution imaging system (VisualSonics, Toronto, Canada) with a 40-MHz transducer (MS-550D) as described. 34 Myograph vascular reactivity analysis of thoracic aortae and mesenteric arteries was performed on a DMT 610M small vessel myograph (Danish Myograph Technology, Aarhus, Denmark) as described 35,36 and analyzed using LabChart 7 software (AdInstruments, Oxford, United Kingdom). Hindlimb perfusion was measured as described.…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
“…The concentration used for each blocker/inhibitor of K + channels is sufficient to antagonize selectively those channels in arterial smooth muscle (Nelson and Quayle, 1995;Lagaud et al, 1999;Cortes et al, 2001;Oliveira et al, 2006). After stabilization of the tonic contraction induced by PHE, increasing cumulative concentrations of KV (1, 10, 30, 100, 300, 500 and 1,000 µg/ml) were added to the organ bath.…”
Section: Investigation Of the Role Of K + Channels In The Kv-induced mentioning
confidence: 99%
“…To further investigate the mechanism of vasorelaxation induced by KV, concentrationresponse curves to CaCl2 were constructed using endothelium-denuded rings (Lagaud et al, 1999). Briefly, the rings were pre-contracted with 60 mM KCl to confirm tissue viability.…”
Section: Effect Of Kv On Sustained Contractions Induced By Cacl2 Andmentioning
confidence: 99%